Do Owners Have a Clever Hans Effect on Dogs? Results of a Pointing Study - Schmidjell, Teresa; Range, Friederike; Huber, Ludwig; Virányi, Zsófia (Frontiers in Psychology, 2012)
Dogs are exceptionally successful at interpreting human pointing gestures to locate food hidden in one of two containers. However, whether dogs are totally reliant on the pointing gesture itself, or if their success is increased by subtle cues from their human handler has repeatedly been questioned. In two experiments we used a standard two-way object-choice task to focus on this potential Clever Hans effect and investigated if and how owners’ knowledge and beliefs influenced their dogs’ performance. In both experiments, as is typical in such pointing tasks, the owners sat behind their dogs, in close auditory and tactile contact with them. In Experiment 1, we systematically manipulated the owners’ knowledge of whether or not their dog should follow the pointing gesture, but instructed the owners to refrain from actively influencing their dog’s choice. We found no influence of subtle cues from the owners, if indeed they existed; dogs in the different groups followed the pointing uniformly. Furthermore, in the absence of pointing, dogs chose randomly, even though the owners had been informed about the location of the reward. In Experiment 2, owners were instructed to actively influence the choice of their dogs, and they, indeed, succeeded in sending their dogs to the container they believed to be baited. However, their influence was significantly weaker if the experimenter had previously pointed to the other location. Overall it seems that the pointing gesture has a strong effect on the choice of dogs in an object-choice task, being capable of leading the dogs to success in the absence of help from the owners but also being able to counteract clear and definite, directional instructions provided by the owner.